Analysis of a poly(ε-decalactone)/silver nanowire composite as an electrically conducting neural interface biomaterial - Katarzyna Krukiewicz; Jorge Fernandez; Małgorzata Skorupa; Daria Więcławska; Anup Poudel; Jose-Ramon Sarasua; Leo R. Quinlan; Manus J. P. Biggs (BMC Biomedical Engineering, 2019)
Abstract Background Advancement in polymer technologies, facilitated predominantly through chemical engineering approaches or through the identification and utilization of novel renewable resources, has been a steady focus of biomaterials research for the past 50 years. Aliphatic polyesters have been exploited in numerous biomedical applications including the formulation of soft-tissue sutures, bone fixation devices, cardiovascular stents etc. Biomimetic ‘soft’ polymer formulations are of interest in the design of biological interfaces and specifically, in the development of implantable neuroelectrode systems intended to interface with neural tissues. Critically, soft polymer formulations have been shown to address the challenges associated with the disregulation of mechanotransductive processes and micro-motion induced inflammation at the electrode/tissue interface. In this study, a polyester-based poly(ε-decalactone)/silver nanowire (EDL:Ag) composite was investigated as a novel electrically active biomaterial with neural applications. Neural interfaces were formulated through spin coating of a polymer/nanowire formulation onto the surface of a Pt electrode to form a biocompatible EDL matrix supported by a percolated network of silver nanowires. As-formed EDL:Ag composites were characterized by means of infrared spectroscopy, scanning electron microscopy and electrochemical methods, with their cytocompatibility assessed using primary cultures of a mixed neural population obtained from the ventral mesencephalon of Sprague-Dawley rat embryos. Results Electrochemical characterization of various EDL:Ag composites indicated EDL:Ag 10:1 as the most favourable formulation, exhibiting high charge storage capacity (8.7 ± 1.0 mC/cm2), charge injection capacity (84.3 ± 1.4 μC/cm2) and low impedance at 1 kHz (194 ± 28 Ω), outperforming both pristine EDL and bare Pt electrodes. The in vitro biological evaluation showed that EDL:Ag supported significant neuron viability in culture and to promote neurite outgrowth, which had the average length of 2300 ± 6 μm following 14 days in culture, 60% longer than pristine EDL and 120% longer than bare Pt control substrates. Conclusions EDL:Ag nanocomposites are shown to serve as robust neural interface materials, possessing favourable electrochemical characteristics together with high neural cytocompatibility.